1987
DOI: 10.1111/j.1540-8191.1987.tb00206.x
|View full text |Cite
|
Sign up to set email alerts
|

A Technique for Selective Graft Perfusion During Aortocoronary Bypass

Abstract: A technique is described that provides early reperfusion of acutely ischemic myocardium during the construction of saphenous vein bypass grafts to the coronary arteries. Selective vein graft perfusion provides early and appropriate cooling of the most ischemic zones identified by either electrocardiographic changes or intramyocardial temperature probes and allows warm blood reperfusion during construction of proximal anastomoses. The technique may be applicable to patients who present with acute ischemia and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…17,18 Patients with CAD require effective delivery of cardioplegic solution beyond coronary stenoses or occlusions. 2,3 In the present study the technique used was similar to the method that Goldman et al 19 described in 1987. The version of the MT Goncu, M Sezen, F Toktas et al…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…17,18 Patients with CAD require effective delivery of cardioplegic solution beyond coronary stenoses or occlusions. 2,3 In the present study the technique used was similar to the method that Goldman et al 19 described in 1987. The version of the MT Goncu, M Sezen, F Toktas et al…”
Section: Discussionmentioning
confidence: 98%
“…This technique can also supply blood to the ischaemic myocardium during construction of the proximal graft anastomosis, promoting early reperfusion and rapid recovery of grafted ischaemic myocardial regions, which may decrease ischaemia time. Goldman et al 19 suggested that selective graft perfusion provides early and appropriate cooling of the most ischaemic zones identified by either electrocardiographic changes or intramyocardial temperature probes, and allows warm blood reperfusion during construction of the proximal anastomosis. These researchers concluded that the technique may be applicable to patients who present with acute ischaemia and evolving infarction, failed angioplasty, or left main coronary artery stenosis.…”
Section: Antegrade Graft Cardioplegia Plus Passive Graft Perfusion In On-pump Cabgmentioning
confidence: 99%
“…This study method was nearly identical to the method suggested by Goldman et al, which stated that careful graft perfusion provides appropriate cooling of the most ischemic zones to protect myocardium by reperfusion of cold blood cardioplegia. The researchers concluded that this method is suitable for patients who present with acute ischemia, failed angioplasty, left main occlusion, and LV systolic dysfunction [15]. Until now, not many studies have been done on cardioplegia through vein grafts to protect the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Homogeneous perfusion of all heart segments may be limited in poorly collateralized coronary artery stenosis cases when only aortic delivery is performed [16][17][18]. In such cases, subsequent dosing, as in the blood cardioplegia protocol, particularly when antegrade graft perfusion is available, provides appropriate cooling of the most ischemic zones and may improve the outcome [19][20]. However, we did not notice any difference in favour of blood cardioplegia in our cohort, which is a similar finding to other reports on using the del Nido protocol in high-risk cases [21][22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%